Implementation of Culturally Based Character Education - Yuda, Meigiriatty Erza; Putra, Alhadi Yan; Nugroho, Heri Setiyo (Journal of Social Work and Science Education, 2024)
This research aims to determine the implementation of culture-based character education in State Vocational Schools. This research uses descriptive qualitative methods with data collection techniques, such as interview methods, field observations, and documentation studies. The research results show that SMK Negeri 1, and SMK Negeri 2 Muara Enim have a good strategy for realizing culture-based character education for their students through routine activities. These routine activities include implementing a culture of greetings, smiles, politeness, manners, and friendship between school members, character education values ​​are also provided during extracurricular activities as well as applying character values through habituation which is carried out every day at school. The obstacles are that teachers still have difficulty adjusting the character values ​​that will be given to students, parental cooperation that does not support the implementation of character education, and students are quite varied so it is quite difficult for teachers to understand students’ characters. Solutions implemented include conducting outreach between the school and parents of students, teachers making efforts to be more optimal and consistent in providing an understanding of character values ​​to students, guidance and counseling teachers, and homeroom teachers continuing to work together in instilling character values ​​in students, instill character values ​​through extracurricular activities.